8 practical Bootstrap projects - Perna, Maria Antonietta (SitePoint, 2018)
Bootstrap stands as one of the most popular, open-source, front-end frameworks on the Web. Since its official release in 2011, it has undergone several changes, and it's now one of the most stable and responsive frameworks available. It's loved by web developers of all levels, as it gives them the capability to build a functional, attractive website design within minutes. A novice developer with just some basic knowledge of HTML and little CSS can easily get started with Bootstrap. In this book, we'll share a selection of nine different practical projects that you can follow along with. It contains: Spicing Up the Bootstrap Carousel with CSS3 Animations by Maria Antonietta Perna A Full-screen Bootstrap Carousel with Random Initial Image by George Martsoukos Animating Bootstrap Carousels with GSAP's Animation Library by George Martsoukos Build a Simple Tumblr Theme with Bootstrap by Ashraff Hathibelagal How to Build a Responsive Bootstrap Website by Syed Fazle Rahman Bootstrap and WordPress Theme Integration in 8 Easy Steps by Ahmed Bouchefra Integrating Bootstrap with React: a Guide for Developers by Manjunath M Integrating Bootstrap with Vue.js using Bootstrap-Vue by Zeeshan Chawdhary This book is for all frontend developers who want to build responsive, mobile-first websites. You'll need to be familiar with HTML and CSS and have a reasonable level of understanding of JavaScript in order to follow the discussion.
Online resource; title from PDF title page (EBSCO, viewed August 9, 2018)
Keywords: Web sites -- Design; Application software -- Development; Ruby (Computer program language); Sites Web; Conception; Logiciels d'application; Développement; Ruby (Langage de programmation); COMPUTERS; Data Processing; Application software; Development; Web sites; Design